OsCER1 Plays a Pivotal Role in Very-Long-Chain Alkane Biosynthesis and Affects Plastid Development and Programmed Cell Death of Tapetum in Rice (Oryza sativa L.) - Ni, Erdong; Zhou, Lingyan; Li, Jing; Jiang, Dagang; Wang, Zhonghua; Zheng, Shaoyan; Qi, Hua; Zhou, Ying; Wang, Cimei; Xiao, Shi; Liu, Zhenlan; Zhou, Hai; et al. (Frontiers in Plant Science, 2018)
Cuticle waxes, which are primarily comprised of very-long-chain (VLC) alkanes, play an important role in plant reproductive development. ECERIFERUM1 (CER1) is recognized as the core element for VLC alkane biosynthesis in Arabidopsis. However, genes involved in the VLC alkane biosynthesis in rice remain unclear, and the alkane-form pathway in rice has still to be further explored. Here, we show that OsCER1, a homology of CER1, functions in VLC alkanes biosynthesis, which also could regulate anther development and plastids differentiation in rice. OsCER1 was highly expressed in the tapetum (stage 10) and bicellular pollen cells (stage 11). The decreased content of VLC alkanes (C25 and C27) in the OsCER1 knocked down plants as well as the increased content of C27 alkanes in the OsCER1 overexpression plants indicates that OsCER1 participates in VLC alkane biosynthesis. Downregulation of OsCER1 in rice led to sterility, and fewer amyloplasts in the pollen grains. In addition, the downregulation of OsCER1 in rice caused delayed tapetal programmed cell death and abnormal development of plastids in the tapetal cells. Furthermore, significantly altered levels of expression of plastidial genes and genes involved in the pollen development were exhibited in the OsCER1 knocked down plants. These results indicate that OsCER1 is critical for VLC alkanes biosynthesis, plastids differentiation, and pollen development. This work provides insights into the VLC alkanes biosynthesis in anther development in rice.